The psychosocial work environment of paramedics in the city of Tshwane - Zuma, Mantai Lillian (My University, 2022)
Background: Emergency medical services (EMS) are an occupational field in which its professionals deal with trauma and medical emergencies daily. Staff working at the emergency departments are mostly exposed to work related hazards including psychosocial risk factors. The medical emergency professionals work irregular hours, their work environment is unstructured, they often travel at high speed and frequently exposed to traumatic incidents. Purpose: The purpose of this study was to describe the psychosocial work environment of paramedics in the City of Tshwane. Setting: The setting for this study was in the City of Tshwane paramedic’s stations: Rosslyn, Bosman and Phillip Nell Park Emergency Medical Services Departments, South Africa. Methods: A cross-sectional survey design was used for this study. using a self-administered questionnaire, the Copenhagen Psychosocial Questionnaire II (COPSOQ II) to collect data. Data analysis: Data was scored according to the Copenhagen Psychosocial Questionnaire scoring system. Statistical analyses included descriptive statistics such as the mean, mode median and standard deviation. The open -ended comment section was analyzed using quantitative content analysis. Stata for Windows English Version 15 was used to analyse the data, while assistance from a statistician from the University of the Witwatersrand Post-Graduate Research Support Services was utilized. Results: A total of 117 Paramedics were recruited and 90 (77%) participants responded in the study. A total of 12 (10%) questionnaires were rejected due to being incomplete. Finally, 78(67%) questionnaires were analysed. From the study 34 (44%) were females, and 44 (56%) were males and the mean age of the participants was 30 to 39 years. High risk factors were unpredictability, lack of appreciation and recognition, justice and respect in the workplace. Lack of leadership quality, lack of work-life balance, burnout and stress were the major issues of poor psychosocial health among paramedics working in the selected three emergency medical services departments in City of Tshwane (COT). In the past 12 months bullying was rated as the most unsuitable behaviour 28 (35.8%) followed by threats of violence 24 (30.7%), real acts of violence 5 (6.4%) and undesired sexual attention 3 (3.8%) in that order. Conclusion: The results of the study emphasised the requirement for an Occupational Health Programme for paramedics working in emergency medical services departments where they are exposed to psychosocial hazards.
A research report submitted in partial fulfilment of the requirements for the degree of Masters of Science in Nursing to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2022